PEREMPUAN - Pakaya, Usman (Jurnal Pelangi Ilmu, 2009)
The aims of this writing is intend to describe what women point of view from two side, they are characters and exploitacy. In this case is present an ambiguity from women itself Both of concepts are sometimes make an upshot in missinterpretation that craft to women in endure their life.